Pelatihan Pemanfaatan Media Pembelajaran Berbasis Kebutuhan Siswa bagi Guru TPA Babussalam Bogor - Fauzy Rahman Kosasih; Juhana Juhana; Suratinah Suratinah (Jurnal Pengabdian Pada Masyarakat, 2021)
A TRAINING OF THE UTILIZATION OF STUDENT NEED-BASED LEARNING MEDIA FOR BABUSSALAM AL-QUR'AN EDUCATION KINDERGARTEN (AEK) BOGOR TEACHERS. This community service program entitled "A Training of the Utilization of Student Need-Based Learning Media for Babussalam Al-Qur'an Education Kindergarten (AEK) Bogor Teachers" aims to improve the ability of Babussalam AEK teachers in Cilebut Barat Village, Bogor Regency, Jawa Barat in developing instructional media in compliance with the needs of students. This activity involved partners, namely the teachers and students of Babussalam AEK. This activity employed training method. The activity started with an initial visit to analyze the situation and needs of the teachers at the site. From the results of the visit, it was agreed that this activity was focused on increasing the ability of teachers in developing instructional media according to student needs. This activity held four meetings. Monitoring and assessment to follow up on the results of PkM activities is carried out at the end of the activity. The results show that after going through community service activities, the teachers are able to understand and implement the theory and techniques of developing learning media based on student needs.